The Use of a Systems Understanding Aid in the Accounting Curriculum. - Arens, Alvin A.; Ward, D. Dewey (The Accounting Review, 1984)
Abstract ABSTRACT: During its study of the auditing profession, the Cohen Commission received some practitioner inputs which suggested that "one of the causes of the discontinuity between accounting theory and practice is that students graduate from accounting programs with no understanding of the mechanics of how an accounting system operates and what the related documentation looks like" [AICPA, 1978, p. 177]. Thus, the question is raised as to whether accounting curricula are providing students with sufficient knowledge about the form and function of the various documents, records, journals, and ledgers used by enterprises to conduct and to record the results of business activities. The implication of the CPA inputs to the Cohen Commission efforts is that a lack of such knowledge can be a deterrent for auditing students in understanding the concepts of audit program development and evidence collection procedures. This paper reports on a Systems Understanding Aid that has been designed to address students' need for additional knowledge about basic accounting system documents and records. The Aid was administered to students and evaluated for effectiveness. Student testing of the Aid has shown it to be an effective pedagogical supplement to the accounting curriculum.